RETRACTED: Circular RNA Circ-0002570 Accelerates Cancer Progression by Regulating VCAN via MiR-587 in Gastric Cancer - Yang, Lei; Zhou, Yong-ning; Zeng, Miao-miao; Zhou, Nan; Wang, Bin-sheng; Li, Bo; Zhu, Xiao-liang; Guan, Quan-lin; Chai, Chen (Frontiers in Oncology, 2021)
Background: Circular RNAs (circRNAs) are closely associated with the occurrences and progress of gastric cancer(GC). We aimed to delve into the function and pathological mechanism of Circular RNA-0002570 (circ-0002570) in GC progression. Methods: CircRNAs differentially expressed in GC were screened using bioinformatics technology. The expression of circ-0002570 was detected in GC specimens and cells via qRT-PCR, and the prognostic values of circ-0002570 were determined. The functional roles of circ-0002570 on proliferation, migration, and invasion in GC cells were explored in vitro and vivo. Interaction of circ-0002570, miR-587 and VCAN was confirmed by dual-luciferase reporter assays, western blotting and rescue experiments. Results: Circ-0002570 expression was distinctly increased in GC tissues than adjacent normal specimens, and GC patients with higher circ-0002570 expressions displayed a short survival. Functionally, knockdown of circ-0002570 resulted in the inhibition of cell proliferation, migration and invasion, and suppressed tumor growth in vivo. Mechanistically, miR-587 was sponged by circ-0002570. VCAN expression in NSCLC was directly inhibited by miR-587. Overexpression of Circ-0002570 prevented VCAN from miR-587-mediated degradation, thus facilitated GC progression. Conclusion: The circ-0002570-miR-587-VCAN regulatory pathway promoted the progression of GC. Our findings provided potential new targets for the diagnosis and therapy of GC.